Demand Response Management in the Presence of Renewable Energy Sources using Stackelberg Game Theory. (August 2019) - Singh, Pushpendra; Talwariya, Akash; Kolhe, Mohan
Abstract: A demand response algorithm for electricity trading using renewable energy sources using stackelberg game methodology. Energy consumption is rapidly increasing day by day and to maintain the balance between energy consumption and generation needs solution to generate electricity from renewable energy sources and demand response methodology is essential. Demand response (DR) algorithm maintain the balance and reduce the peak to average energy consumption ratio. Large number of constraints (i.e. number of appliance at consumer end, different consumers, renewable energy sources, electric vehicles, etc.) interface make the DR algorithm complex. Stackelberg game theory is provided the solution based on one leader N follower strategy where leader first decide their best response and followers select their best response on the basis of leaders strategy and then leader again optimize the new strategy. Process is repeat again and again to find nash equilibrium between consumers and utilities. Proposed methodology increase the generation from renewable energy sources and manage the appliances. Simulation results showed that stackelberg game with demand response algorithm is effective for optimal energy consumption control of appliances.